Asthma care during COVID-19: differences in attitudes and expectations between physicians and patients. (4th May 2022) - Arora, Nonie; Lowe, Desmond; Sarsour, Nadeen; Jaffee, Hannah; Eftekhari, Sanaz; Carpenter, Laurie M.; Bansal, Priya; Baptist, Alan P.
Abstract: Objective: The aim of this study was to explore differences in attitudes, behaviors and expectations related to COVID-19 between physicians and patients with asthma. Methods: An anonymous survey was distributed through email and social media to adult patients with asthma during a three-week period in April-May 2020. A separate survey was sent to physicians. The surveys asked about demographic information, specific challenges and concerns due to COVID-19, and attitudes/behaviors during this time. Results: A total of 1171 patients and 225 physicians completed the surveys. Overall, patients with asthma and physicians had large differences in expectations related to COVID-19. Patients were more likely than physicians to believe that individuals with asthma are at a higher risk to get COVID-19 (37.5% vs. 12.0%, p  < 0.001), have increased anxiety due to COVID-19 (79.6% vs 70.0%, p  = 0.002), and should not go to work (62.7% vs 11.9%, p  < 0.001). Neither patients nor physicians felt confident they could distinguish COVID-19 symptoms from asthma (61.2% and 74.5% did not feel confident, respectively). Patients with severe asthma were significantly more impacted by the pandemic (e.g., became unemployed [OR 2.15], had difficulty getting asthma medications [OR 2.37]) compared to those with nonsevere asthma. Conclusion: Patients with asthma and their physicians have markedly different attitudes and opinions regarding care during the COVID-19 pandemic. Such differences have important implications when providing patient-centered care. Supplemental data for this article can be accessed at publisher's website . Abbreviations: ACT: Asthma Control Test; CDC: Centers for Disease Control; CI: Confidence Interval; COVID-19: Coronavirus Disease 2019; ED: Emergency Department; ICU: Intensive Care Unit; NIH: National Institutes of Heath; IRB: Institutional Review Board; OR: Odds Ratio; PCP: Primary Care Physician; SD: Standard Deviation